Steve Jobs - Isaacson, Walter (New York : Simon & Schuster, 2011)
"FROM THE AUTHOR OF THE BESTSELLING BIOGRAPHIES OF BENJAMIN FRANKLIN AND ALBERT EINSTEIN, THIS IS THE EXCLUSIVE BIOGRAPHY OF STEVE JOBS. Based on more than forty interviews with Jobs conducted over two years--as well as interviews with more than a hundred family members, friends, adversaries, competitors, and colleagues--Walter Isaacson has written a riveting story of the roller-coaster life and searingly intense personality of a creative entrepreneur whose passion for perfection and ferocious drive revolutionized six industries: personal computers, animated movies, music, phones, tablet computing, and digital publishing. At a time when America is seeking ways to sustain its innovative edge, and when societies around the world are trying to build digital-age economies, Jobs stands as the ultimate icon of inventiveness and applied imagination. He knew that the best way to create value in the twenty-first century was to connect creativity with technology. He built a company where leaps of the imagination were combined with remarkable feats of engineering. Although Jobs cooperated with this book, he asked for no control over what was written nor even the right to read it before it was published. He put nothing off-limits. He encouraged the people he knew to speak honestly. And Jobs speaks candidly, sometimes brutally so, about the people he worked with and competed against. His friends, foes, and colleagues provide an unvarnished view of the passions, perfectionism, obsessions, artistry, devilry, and compulsion for control that shaped his approach to business and the innovative products that resulted. Driven by demons, Jobs could drive those around him to fury and despair. But his personality and products were interrelated, just as Apple's hardware and software tended to be, as if part of an integrated system. His tale is instructive and cautionary, filled with lessons about innovation, character, leadership, and values"--
Based on more than forty interviews with Jobs conducted over two years, as well as interviews with more than a hundred family members, friends, adversaries, competitors, and colleagues, the author has written a riveting story of the roller-coaster life and searingly intense personality of a creative entrepreneur whose passion for perfection and ferocious drive revolutionized six industries: personal computers, animated movies, music, phones, tablet computing, and digital publishing. At a time when America is seeking ways to sustain its innovative edge, and when societies around the world are trying to build digital-age economies, Jobs stands as the ultimate icon of inventiveness and applied imagination. He knew that the best way to create value in the twenty-first century was to connect creativity with technology. He built a company where leaps of the imagination were combined with remarkable feats of engineering. Although Jobs cooperated with this book, he asked for no control over what was written nor even the right to read it before it was published. He put nothing off-limits. He encouraged the people he knew to speak honestly. And Jobs speaks candidly, sometimes brutally so, about the people he worked with and competed against. His friends, foes, and colleagues provide an unvarnished view of the passions, perfectionism, obsessions, artistry, devilry, and compulsion for control that shaped his approach to business and the innovative products that resulted. Driven by demons, Jobs could drive those around him to fury and despair. But his personality and products were interrelated, just as Apple's hardware and software tended to be, as if part of an integrated system. His tale is instructive and cautionary, filled with lessons about innovation, character, leadership, and values. -- From publisher.
Childhood: abandoned and chosen -- Odd couple: the two Steves -- The dropout: turn on, tune in -- Atari and India: Zen and the art of game design -- The Apple I: turn on, boot up, jack in -- The Apple II: dawn of a new age -- Chrisann and Lisa: he who is abandoned -- Xerox and Lisa: graphical user interfaces -- Going public: a man of wealth and fame -- The Mac is born: you say you want a revolution -- The reality distortion field: playing by his own set of rules -- The design: real artists simplify -- Building the Mac: the journey is the reward -- Enter Sculley: the Pepsi challenge -- The launch: a dent in the universe -- Gates and Jobs: when orbits intersect -- Icarus: what goes up -- NeXT: Prometheus unbound -- Pixar: technology meets art -- A regular guy: love is just a four-letter word -- Family man: at home with the Jobs clan -- Toy Story: Buzz and Woody to the rescue -- The second coming: what rough beast, its hour come round at last -- The restoration: the loser now will be later to win -- Think different: Jobs as iCEO -- Design principles: the studio of Jobs and Ive -- The iMac: hello (again) -- CEO: still crazy after all these years -- Apple stores: Genius bars and Siena sandstone -- The digital hub: from iTunes to the iPod -- The iTunes store: I'm the pied piper -- Music man: the sound track of his life -- Pixar's friends: and foes -- Twenty-first-century Macs: setting Apple apart -- Round one: memento mori -- The iPhone: three revolutionary products in one -- Round two: the cancer recurs -- The iPad: into the post-PC era -- New battles: and echoes of old ones -- To infinity: the cloud, the spaceship, and beyond -- Round three: the Twilight struggle -- Legacy: the brightest heaven of invention.
Includes bibliographical references (p. 576-598) and index.
Keywords: Jobs, Steve, -- 1955-2011.; Apple Computer, Inc. -- History; Computer engineers -- United States -- Biography; Businesspeople -- United States -- Biography; BIOGRAPHY & AUTOBIOGRAPHY / Business; BUSINESS & ECONOMICS / General; TECHNOLOGY & ENGINEERING / General